2010
DOI: 10.1007/s11207-010-9575-7
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Red and Green Coronal Line Intensities at the 29 March 2006 and the 1 August 2008 Total Solar Eclipses: Considerations of the Temperature of the Solar Corona

Abstract: During the total solar eclipse at Akademgorodok, Siberia, Russia, on 1 August 2008, we imaged the flash spectrum with a slitless spectrograph. We have spectroscopically determined the duration of totality, the epoch of the second and third contacts and the duration of the flash spectrum. Here we compare the 2008 flash spectra with those that we similarly obtained from the total solar eclipse of 29 March 2006, at Kastellorizo, Greece. Any changes of the intensity of the coronal emission lines, in particularly t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…the same amount of shift as the H α line (as shown hereafter), thus indicate chromospheric origin like the Balmer emission lines. Indeed, these lines have been seen during solar total eclipses (Voulgaris et al 2010), supporting their chromospheric origin. Also, the 5 876 Å line appears in emission in very strong solar flares (Johns-Krull et al 1997 and references therein).…”
Section: Optical Spectroscopic Observationsmentioning
confidence: 54%
“…the same amount of shift as the H α line (as shown hereafter), thus indicate chromospheric origin like the Balmer emission lines. Indeed, these lines have been seen during solar total eclipses (Voulgaris et al 2010), supporting their chromospheric origin. Also, the 5 876 Å line appears in emission in very strong solar flares (Johns-Krull et al 1997 and references therein).…”
Section: Optical Spectroscopic Observationsmentioning
confidence: 54%
“…We have also estimated the temperature using the line ratio technique. Recently, Voulgaris et al (2010) have reported the relative intensity ratios of the red and green lines to be 0.577 and 2.161 during the solar eclipses in 2006 and 2008, respectively. However, during this observation we have measured this ratio to be between 0.45 to 1, which indicates that the relative intensity of the red line has decreased, at least in this observed coronal structure.…”
Section: Discussionmentioning
confidence: 99%
“…We note that the solar corona has a multitemperature coronal structure, as intensity ratios vary in different structures and with solar radii. The conclusion drawn by Voulgaris et al (2010) is based on limited data for a few coronal structures. One must have observations for longer periods and over a large portion of the solar corona to conclude that the temperature varies with activity on shorter time scales.…”
Section: Discussionmentioning
confidence: 99%
“…Its data were recorded with a second RED Epic camera, to continue the studies of coronal temperature from the [Fe x]/ [Fe xiv] ratio, as previously reported by our group (Voulgaris et al 2010(Voulgaris et al , 2012. The RED Epic camera has a high dynamic range of 13.5 stops, up to 120 fps at 5k resolution with an effective 13.8 megapixel 14 bit CMOS sensor.…”
Section: Mt Carbinementioning
confidence: 98%
“…Equipment included a sophisticated spectrograph (constructed by A.V.) for the temperature measurements (Voulgaris et al 2010(Voulgaris et al , 2012. A satellite site was 20 km north along the coast.…”
Section: Coastal Observationsmentioning
confidence: 99%